Efficient acid catalytic synthesis of pyrazolopyrimidines from 1H-pyrazol-5-yl-N, N-dimethylformamidines with cyanamide. Issue 22 (31st May 2018) - Tsai, Shuo-En; Yen, Wan-Ping; Tseng, Ching-Chun; Xie, Jia-Jun; Liou, Min-Yu; Li, Yi-Ting; Uramaru, Naoto; Wong, Fung Fuh
Abstract: The efficient acid catalytic synthesis of pyrazolo [3, 4-d]pyrimidine was developed by treating 1 H -pyrazol-5-yl- N, N -dimethylformamidine with various aminating agents including N, O -bis(trimethylsilyl)hydroxylamine (NHSiMe3 (OSiMe3 )), cyanamide (NH2 CN), hydroxylamine (NH2 OH), methoxyamine (NH2 OMe), hydrazine (NH2 NH2 ), and urea (NH2 C(O)NH2 ) in acidic solution at reflux. Based on the experimental result, cyanamide (NH2 CN) and methanesulfonic acid were indicated the best aminating agent and acid mediated solvent. On the other hands, the reactivity tendency was involved the activity of original leaving species grafting on the aminating agents, such as –OH, –OMe, –OSiMe3, –NH2, –OSiMe3, –C(O)NH2, and –CN, in acid catalytic heterocyclic reaction. Graphical abstract: